Polarization effects in elastic proton-electron scattering - Gakh, G.I.; Dbeyssi, A.; Marchand, D.; Bytev, V.V.; Tomasi-Gustafsson, E. (Вопросы атомной науки и техники, 2012)
Proton elastic scattering from electrons at rest is calculated in the Born approximation. The interest of this reaction is related to the possibility of polarizing high energy antiproton beam and to high energy proton polarimetry. The differential cross section and polarization observables have been derived assuming one photon exchange. Numerical estimates are given for the cross section and the spin correlation coefficients in a wide kinematical range.